2019
DOI: 10.1002/ece3.5560
|View full text |Cite
|
Sign up to set email alerts
|

Temperature amplifies the effect of high CO2 on the photosynthesis, respiration, and calcification of the coralline algae Phymatolithon lusitanicum

Abstract: The combination of ocean acidification (OA) and global warming is expected to have a significant effect on the diversity and functioning of marine ecosystems, particularly on calcifying algae such as rhodoliths (maërl) that form extensive beds worldwide, from polar to tropical regions. In addition, the increasing frequency of extreme events, such as heat waves, threatens coastal ecosystems and may affect their capacity to fix blue carbon. The few studies where the simultaneous effects of both temperature and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Our results show that calcification in P. lusitanicum is more temperature controlled and not as dependent on light as photosynthesis. In a previous experiment where the effect of temperature and high CO 2 in the net production and calcification of P. lusitanicum was assessed, we also found that calcification increases with temperature, and this effect is more pronounced under high CO 2 (Sordo et al, 2019). The highest relative growth rates were observed from September to November of 2013 when we recorded the highest temperature and irradiance conditions.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our results show that calcification in P. lusitanicum is more temperature controlled and not as dependent on light as photosynthesis. In a previous experiment where the effect of temperature and high CO 2 in the net production and calcification of P. lusitanicum was assessed, we also found that calcification increases with temperature, and this effect is more pronounced under high CO 2 (Sordo et al, 2019). The highest relative growth rates were observed from September to November of 2013 when we recorded the highest temperature and irradiance conditions.…”
Section: Discussionsupporting
confidence: 71%
“…The information currently available on P. lusitanicum is restricted to descriptive studies of its morphology and the composition of the beds (Carro et al, 2014;Peña et al, 2015), associated flora Bárbara, 2010, 2013), and the effect of high CO 2 and warming on the photosynthesis, calcification, and respiration (Sordo et al, 2016(Sordo et al, , 2018(Sordo et al, , 2019. Despite the recognized importance of the habitat, there is no information on the environmental conditions under which these algae live or on the key abiotic variables that regulate the metabolic rates of P. lusitanicum under natural conditions or increasing temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Also, comparisons among different species, from the same habitat, suggest a variability in the strength of the coupling between photosynthesis and calcification (Vaśquez-Elizondo and Enrıquez, 2016;Qui-Minet et al, 2021). The direct relationship between these processes was demonstrated early on (Digby, 1977;Pentecost, 1978;Borowitzka, 1981;Borowitzka, 1987) and is supported by recent studies (e.g., Martin et al, 2013;Vaśquez-Elizondo and Enrıquez, 2016;Sordo et al, 2019), which showed a decline in calcification upon inhibition of photosynthesis (Hofmann et al, 2016;McNicholl et al, 2019). This link has been related to an elevation of the pH at the calcification site due to photosynthetic activity.…”
Section: Introductionmentioning
confidence: 71%
“…Even less information is available regarding the mechanisms driving rhodolith photosynthesis and calcification (Cornwall et al, 2017;Hofmann and Heesch, 2018;Zweng et al, 2018). Essentially, most physiological data derive from studies that assessed the effects of climate change-related and other environmental factors on rhodolith performance (King and Schramm, 1982;Steller et al, 2007;Semesi et al, 2009;Büdenbender et al, 2011;Kamenos et al, 2013;Noisette et al, 2013a;Noisette et al, 2013b;Sordo et al, 2016;Vaśquez-Elizondo and Enrıquez, 2016;Cornwall et al, 2017;Legrand et al, 2017;Schoenrock et al, 2018;Sordo et al, 2018;Zweng et al, 2018;Legrand et al, 2019;Sordo et al, 2019;Comeau et al, 2019a;Comeau et al, 2019b;Qui-Minet et al, 2019;Schubert et al, 2019;Carvalho et al, 2020;Kim et al, 2020;Legrand et al, 2021;Schubert et al, 2021b). These studies show that rhodoliths express a wide array of responses to environmental changes (see also Martin and Hall-Spencer, 2017), suggesting a high variability in the mechanisms related to photosynthesis and calcification.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of climate effects can apply various methods, such as the data interpolating empirical orthogonal functions [108] and fixed rank kriging [109] to fill the gaps in the chlorophyll-a and SST data occurring due to cloud cover. In addition, several other climatic phenomena, such as typhoons [110], storms [111,112], heat waves [113], and droughts [114] have been reported to significantly affect the blue carbon ecosystems; thus, these climatic events should be comprehensively studied. Additionally, physiochemical parameters, such as salinity [115][116][117], total suspended solids [118], and colored dissolved organic matter [119], that can be extracted through remote sensing can be used to build more complex and comprehensive models.…”
Section: Future Research Directivesmentioning
confidence: 99%